Melanotic neuroectodermal tumor of infancy presenting as rapidly enlarging cheek mass - Tessa Henry; Ryan Meyer; Oliver Lao; Mandolin Ziadie; Michael Rainisch (Elsevier, 2022)
Malignancies in infants are unusual and often difficult to diagnose. We discuss the presentation, diagnosis, and treatment of a patient with a melanotic neuroectodermal tumor of infancy (MNTI) and discuss the limited literature of this topic.